Frequency and Antimicrobial Susceptibility Pattern of Gram-Negative Bacilli Isolated From Urine Specimens at a Tertiary Care Setting - Aamir Hussain; Ihsan Ullah; Humera Adeeb; Mubarak Zeb (Gandhara University, 2022)
OBJECTIVES: To find out the frequency and pattern of conventional antibiotic susceptibility of gram-negative bacilli cultured from urine specimens of patients at a tertiary care setting. METHODOLOGY: This study was conducted at the Microbiology Department of Combined Military Hospital Multan from June 2016 to May 2017. The data in this retrospective descriptive study was collected from urine culture records of the Microbiology Department, CMH Multan. Only those urine specimens who revealed positive gram-negative bacilli cultures were included in the study. Drug susceptibility patterns of these isolates were recorded against routinely used antibiotics (e.g. Nitrofurantoin, Imipenem, Sulbactum-cefoperazone, Gentamicin and Ciprofloxacin) and evaluated accordingly. RESULTS: A total of 1703 urine specimens were submitted for culture and antibiotics susceptibility testing during the period of study. A total of 128 specimens showed growth of gram-negative rods. Imipenem (95% sensitivity), Sulbactam- Cefoperazone (88% sensitivity) and Nitrofurantoin (87% sensitivity) were highly effective antibiotics against the cultured gram-negative bacilli in the study. CONCLUSION: This study showed that E. coli is the commonest cause of urinary tract infection (UTIs), followed by Klebsiella and Enterobacter species among gram-negative bacilli in our set up. In-vitro efficacy of Imipenem, Sulbactam- Cefoperazone and Nitrofurantoin was found to be the highest against these gram-negative bacilli as compared to other antimicrobials. On the contrary, in-vitro efficacy of ciprofloxacin and gentamycin was found to be extremely low.